Design and synthesis of cinnamic acid triptolide ester derivatives as potent antitumor agents and their biological evaluation. (1st July 2022) - Cheng, Chenglong; Li, Gudong; Zheng, Guojun; Yu, Changyuan
Graphical abstract: Abstract: A series of novel cinnamic acid triptolide ester derivatives were synthesized, and their growth inhibitory properties against human hepatoma HepG2 cells were assessed as the measure of cytotoxicity with triptolide as the positive control. One of the phenolic hydroxyl phosphorylated products, CL20 was found to possess the best cytotoxicity and surpassed the parent natural triptolide, suggesting that compound CL20 is a promising antitumor lead compound and deserves further research of pharmacological activity. In addition, the structure-activity relationship for these compounds was also investigated.